Cochrane vertebroplasty review misrepresented evidence for vertebroplasty with early intervention in severely affected patients. Issue 3 (9th March 2019) - Clark, William; Bird, Paul; Diamond, Terrence; Gonski, Peter; Gebski, Val
Abstract : The Cochrane vertebroplasty review of April 2018 was replaced with an updated version in November 2018 to address complaints of errors in analysis. The updated version continues to misrepresent the evidence supporting early intervention with vertebroplasty for patients with uncontrolled, severe pain and fracture duration <6 weeks. The VAPOUR trial is the only blinded trial of vertebroplasty restricted to this patient group. It showed the benefit of vertebroplasty over placebo, particularly when the intervention occurred within 3 weeks of fracture. The Cochrane vertebroplasty review has ignored the positive outcomes in the VAPOUR trial. Open randomised trials of fractures <6-week duration support the positive findings of the VAPOUR trial. This is not described in the Cochrane review. The VAPOUR trial is clinically heterogeneous from other blinded trials. Cochrane protocol stipulates that clinically heterogeneous trials be described separately, as independent evidence, and not combined in analysis with dissimilar trials. Failure to observe this represents a serious protocol breach in the Cochrane review.